2021
DOI: 10.1007/s13187-021-02077-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Youth Perceptions About Cancer Prevention and Preferences for Education: a Qualitative Study

Abstract: This study aimed to characterize adolescents’ perspectives on cancer and cancer prevention and to explore their preferences for cancer education. A total of 188 middle and high school students participated in 25 focus groups. Focus groups were led by study team members and included five to ten participants each. Adolescents were asked to discuss their cancer and cancer prevention knowledge, sources of cancer education, and preferences for cancer prevention education. Focus groups were audio-recorded, and profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
2
14
0
1
Order By: Relevance
“…The 2018 report revealed that palliative care (6.8%), quality of life among cancer patients (11.0%) and cancer treatments (15.9%) were minimally covered in the teaching (Ministry of Education, Culture, Sports, Science and Technology, 2022), and it should be assumed that it is difficult for school teachers to teach children about actual clinical practice. Importantly, a previous study has reported that adolescents prefer learning through online videos and in school (Abraham et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The 2018 report revealed that palliative care (6.8%), quality of life among cancer patients (11.0%) and cancer treatments (15.9%) were minimally covered in the teaching (Ministry of Education, Culture, Sports, Science and Technology, 2022), and it should be assumed that it is difficult for school teachers to teach children about actual clinical practice. Importantly, a previous study has reported that adolescents prefer learning through online videos and in school (Abraham et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Our study allowed us to draw some important conclusions that are consistent with the results available in the literature. [2][3][4][5][6][7][8][9][10][11][14][15][16]…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it is a valuable tool for determining what drives a person to do or refrain from taking health-related actions, as well as the circumstances in which they are most likely to display protective behaviours. 10 The health attitudes of people on the interventions to be taken for testicular cancer are important for health professionals, especially those dealing with cancer diagnoses. By organizing health trainings on the significance of early diagnosis in testicular cancer, early symptoms of the illness, and how to do TSE, nurses are anticipated to raise men's knowledge of this issue.…”
Section: Background For the Studymentioning
confidence: 99%
See 2 more Smart Citations